2021
DOI: 10.3390/jcm10215162
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Mortality, Acute Kidney Injury and Graft Loss in Adult Kidney Transplant Recipients with Coronavirus Disease 2019: Systematic Review and Meta-Analysis

Abstract: The adverse impact of Coronavirus disease 2019 (COVID-19) on kidney function has been reported since the global pandemic. The burden of COVID-19 on kidney transplant recipients, however, has not been systematically analyzed. A systematic review and meta-analysis with a random-effect model was conducted to explore the rate of mortality, intensive care unit admission, invasive mechanical ventilation, acute kidney injury, kidney replacement therapy and graft loss in the adult kidney transplant population with COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 89 publications
0
18
0
1
Order By: Relevance
“…1,2 The coronavirus disease 2019 (COVID-19)-associated mortality risk in this population is very high: approximately 23% for kidney transplant recipients (KTRs) of 65 y and increasing with 3.7% for every 10 y of age. 3 Vaccination is a very effective way to prevent a severe course of COVID-19 infection in the general population. 4,5 Unfortunately, several studies have shown that the seroconversion rates after 2 COVID-19 mRNA vaccinations are relatively low in KTRs, with percentages varying between 4% and 57%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The coronavirus disease 2019 (COVID-19)-associated mortality risk in this population is very high: approximately 23% for kidney transplant recipients (KTRs) of 65 y and increasing with 3.7% for every 10 y of age. 3 Vaccination is a very effective way to prevent a severe course of COVID-19 infection in the general population. 4,5 Unfortunately, several studies have shown that the seroconversion rates after 2 COVID-19 mRNA vaccinations are relatively low in KTRs, with percentages varying between 4% and 57%.…”
Section: Introductionmentioning
confidence: 99%
“…1 , 2 The coronavirus disease 2019 (COVID-19)–associated mortality risk in this population is very high: approximately 23% for kidney transplant recipients (KTRs) of 65 y and increasing with 3.7% for every 10 y of age. 3 …”
Section: Introductionmentioning
confidence: 99%
“…In 2021, COVID-19 infections were managed similarly in kidney transplant recipients and in the general population ( 49 , 50 ), although transplant recipients had heightened risk of poor outcomes ( 51 ). Given the risks inherent in commenting on any single publication, the authors encourage regular review of guidance from the US National Institutes of Health ( 47 ) and the European Medicines Agency ( 52 ).…”
Section: Post Script: October 2021 Reflections From the Groupmentioning
confidence: 99%
“…In fact, the authors demonstrated increased rates of adverse outcomes among transplanted patients: mortality—21%; admission to intensive care units—26%; intensive mechanical ventilation among those who required admission in intensive care units—72%; acute kidney injury—44%; kidney replacement therapy—12%; and graft loss—8%. Moreover, a higher risk of mortality for elder patients has been registered too [ 9 ].…”
Section: Chronic Diseasementioning
confidence: 99%